RESHAPING THE VALUE PROPOSITION: STRATEGIC RESPONSES OF LANGUAGE COURSE PROVIDERS TO THE AI REVOLUTION - Tjahyanto, Mario Christian Noer; Yenny, Hartanto (Politeknik Ubaya, 2026)
The rapid proliferation of Generative Artificial Intelligence (GenAI) has catalyzed a fundamental shift in the education sector, specifically disrupting the traditional business model of Language Course Providers (LCPs). As AI-driven tools provide high-quality translation and personalized tutoring at near-zero marginal costs, traditional language services are experiencing rapid commoditization. This research explores how LCPs can reshape their value propositions to maintain strategic relevance and financial sustainability. Utilizing a qualitative conceptual research design, the study applies the Value Proposition Canvas (VPC) and Disruptive Innovation frameworks to analyze the gap between automated AI capabilities and human-centric pedagogical needs. Empirical evidence from a case study reveals a staggering 80% decrease in document translation requests and a 60% decline in course registrations, signaling a